Nowoczesne antynomie. Uwagi o nowych odczytaniach poezji Bolesława Leśmiana - Winiecka, Elżbieta (Wydawnictwo Naukowe UAM, 2009)
The article presents two poles of reflection on modernity of Bolesław Leśmian’s poetry. On one side can be placed the standpoint of researchers who saw in this poetic work mostly the realisation of the myth of return to primaevality (M. Głowiński, Z. Łapiński), whose consequence would have to be such a conception of poetic language in which a word personalises an object. On the other side appear voices (M.P. Markowski, R. Nycz) which expose the mediatory role of language as a place of birth of the sense of reality, incomplete without the creative activity of language. In this way two views clash: of poetry as a space of retrieving of authenticity and as a way of revealing (creating) new states of existence of the world. At their intersection can be placed the third interpretation (A. Skrendo) in which the poet is fully aware of the antinomy between his own poetic project and impossibility of its realisation. Reaching for Leśmian’s antiessentialistic conception of the subject and reality, we can recreate in his works the way leading to utopian dreams of the immediacy of communication to the fully aware inevitability of failure of any attempts which are to lead to the set goal. It is just this last pessimistic statement which is a foundation of the poetic worldview of the poet which defines the remarkable status of this poetry in the perspective of studies of modernity.
Modern antynomies. Remarks on new readings of Bolesław Leśmian’s poetry